Belimumab or anifrolumab for systemic lupus erythematosus? A risk-benefit assessment - Kirou, Kyriakos A.; Dall`Era, Maria; Aranow, Cynthia; Anders, Hans-Joachim (Frontiers in Immunology, 2022)
Treatment of systemic lupus erythematosus (SLE) currently employs agents with relatively unselective immunosuppressive properties. However, two target-specific biological drugs have been approved: belimumab (anti-B-cell-activating factor/BAFF) and anifrolumab (anti-interferon alpha receptor-1/IFNAR1). Here, we performed a comparative risk-benefit assessment for both drugs based on the role of BAFF and IFNAR1 in host defense and the pathogenesis of SLE and by considering the available data on safety and efficacy. Due to differences in target expression sites, anti-IFNAR1, but not anti-BAFF, might elicit organ-specific effects, consistent with clinical efficacy data. The IFNAR1 is specifically involved in innate and adaptive antiviral immunity in most cells of the body. Consistent with this observation, the available safety data obtained from patients negatively selected for LN and neuropsychiatric SLE, primary immunodeficiencies, splenectomy and chronic HIV, HBV, HCV infections suggest an increased risk for some viral infections such as varicella zoster and perhaps influenza. In contrast, BAFF is mainly involved in adaptive immune responses in lymphoid tissues, thus anti-BAFF therapy modulates SLE activity and prevents SLE flares without interfering with local innate host defense mechanisms and should only marginally affect immune memory to previous pathogen exposures consistent with the available safety data from SLE patients without chronic HIV, HBV or HCV infections. When using belimumab and anifrolumab, careful patient stratification and specific precautions may minimize risks and maximize beneficial treatment effects for patients with SLE.